2018
DOI: 10.1111/pops.12511
|View full text |Cite
|
Sign up to set email alerts
|

History in the Service of Politics: Constructing Narratives of History During the European Refugee “Crisis”

Abstract: It is common for politicians to refer to "our proud history of supporting refugees," yet the historical record regarding responses to refugees is not straightforwardly positive. So how is history drawn upon in political debates regarding refugees? Applying discursive psychology, this article analyzes the use of history in five U.K. parliamentary debates that took place from September 2015 to January 2016 on the European refugee "crisis." The analysis identifies six "functions" of the use of the history: resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
20
1
Order By: Relevance
“…Their ongoing studies have revealed that collective memory exerts a distinct impact on public opinion that cannot be explained using the typical explanations offered by right‐wing authoritarianism, social dominance orientation, and social identification. Other studies have also demonstrated how collective memory influences contemporary political issues and intergroup relations (see Kirkwood, ; Schori‐Eyal, Klar, Roccas, & McNeill, ). More specifically, the ways in which history is remembered affect differences in national identification and nationalism (Hirschberger, Kende, & Weinstein, ; Smeekes, Verkuyten, & Poppe, ).…”
Section: National Days National Identity and Collective Memorymentioning
confidence: 96%
“…Their ongoing studies have revealed that collective memory exerts a distinct impact on public opinion that cannot be explained using the typical explanations offered by right‐wing authoritarianism, social dominance orientation, and social identification. Other studies have also demonstrated how collective memory influences contemporary political issues and intergroup relations (see Kirkwood, ; Schori‐Eyal, Klar, Roccas, & McNeill, ). More specifically, the ways in which history is remembered affect differences in national identification and nationalism (Hirschberger, Kende, & Weinstein, ; Smeekes, Verkuyten, & Poppe, ).…”
Section: National Days National Identity and Collective Memorymentioning
confidence: 96%
“…Nonetheless, any understanding of the recent historical past must be aligned with the endorsed cultural memory representations in order to maintain the historical continuity (Connerton, 1989;Jetten & Wohl, 2012). A sense of historical continuity emerging from the interaction between the two modi memorandi is motivated by a need for group identity (e.g., Kirkwood, 2019;Schwartz, 1996;Schwartz et al, 1986).…”
Section: Historical Memories As Building Blocks Of National Identitymentioning
confidence: 99%
“…Particularly in times of change and uncertainty, politicians draw upon the past to find guidance and legitimize actions in the present (Brändström, Bynander, & Hart, 2004; Ghilani et al, 2017). In doing so, they primarily refer to heroic images of the past in their attempt to convince others of their policies (Kirkwood, 2019). In this article, however, we aim to contribute to a better understanding of how nations whose negative past dominates their contemporary narrative negotiate their history in political discourse and to identify strategies that may deviate from the ones established in previous research.…”
Section: History In Politicsmentioning
confidence: 99%